Dominant Macro Factors on the Performance of Sharia Stocks in the Period of Two Presidencies in Indonesia - Erna Garnia; Tahmat; Deden Rizal Riyadi; Rio Akbar Pasuma; Puji Sri Astuti (Indonesian Journal of Banking and Financial Technology, 2023)
Regulations issued by the government have an impact on the development of the capital market in Indonesia. This study analyzes the influence of macroeconomic and non-macroeconomic factors consisting of global, macroeconomic, world oil prices, Chinese indexes, Arabian indexes and competitive resources on the expected return of the last two presidential terms, namely Susilo Bambang Yudhoyono and Joko Widodo by using Arbitrage Pricing. theory. The analysis was carried out on stocks included in the Jakarta Islamic Index for the period October 2004 - October 2021 by dividing them into high return and low return groups for each presidential term. The aim of the study was to examine the effect of the global index, macroeconomics, Chinese index, Arabian index and competitiveness on JII stock returns during the presidency of SBY and JKW.